Social Semiotics "Masako Package”: Systemic Functional Linguistics Perspective - Nancy Natalia Dharmawan; I Ketut Suardana; Yoga Putra Semadi (Journal of Pragmatics Research, 2025)
This research investigates the references which are realized by signs within the Masako package. The scope of this research is language in function, which is presented in both verbal and non-verbal languages. The theory used for this research is Systemic Functional Linguistics (SFL), which is supported with the theory of semiotic for non-verbal language. The research implies qualitative research, and phenomenology. The data were taken from Masako package. The verbal language such as clauses are analyzed with theory of SFL proposed by Halliday, while nonverbal language such as; colours, pictures, photos are analysed with semiotic proposed by Peirce. The research results indicate that the Massako package hires nonverbal and verbal languages. The yellow colour indicates that Masako is very suitable for cooked food. The red indicates that the spice contains chilly, which is not good for baby food. The green indicates that the spice is very good with fresh meat and vegetables. The ideologies of Masako are; (i) the company of Masako wants to share the market with some segmentation by providing several taste and different weight in the packages, (ii) the company want to dominate the market by showing “Halal” so most of Indonesian communities are not in doubt about the material. This research is significant for semiotics, discourse analysis, and language teaching. This research is expected to be very useful for communities and to stimulate other researchers to do similar research.